PEMBELAJARAN TAHFIZH DI SD N 25 TALAMAU KAMPUNG BATEH SAMUIK NAGARI SINURUIK - Lisdayanti; Syofrianisda; Iswandi Iswandi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2022)
This study aims to determine the learing of tahfidz al Qur’an in SD N 25 Talamaukampung Bateh Samuik. The method used in this research is a qualitative method with casestudy and observation techniques. The results obtained in this study that learning tahfidzthe koran includes three main activities, namely planning, implementation and assessment.Learning planning is carried out before the school year begins through teacherconsultation with the school principal. The learning process includes an initial activity(introduction) which begins with greetings, prayers and repetition of memorization thathas been memorized beforehand. Than the core activity, namely the delivery of tahfidz alQur’an material by the way the teacher reads and students follow and then repeat. Andfinally the closing activity which was closed whit a small evaluation and delivery ofmaterial to be studied at the next meeting. The assessment is divided into two categories,namely daily assessment and semester assessment. The assessment menthod used inlearning the koran tahfidz with the method of tasmi and musabaqah.